Gravity profile and crustal structure across the northern New Québec Orogen - Mareschal, Jean-Claude; Coletta, Gino; Clevenot, Isabelle; Goulet, Normand (Geoscience Canada, 1990)
Summary Detailed gravity data, collected along an east-west transect across the northern New Québec Orogen near Leaf Bay, provide constraints on the deep structure of this segment of the orogen. The Bouguer anomaly profilecontains long and short wavelength compo-nents. A steep gravity gradient and a strongpositive anomaly near the centre of the orogen are related to the presence of densemafic volcanic rocks in the shallow crust. Two alternative models are presented that are compatible with the long wavelength gravity data. The authors prefer to interpret the long wavelength components in terms of crustal thickening beneath the orogen and increased crustal density in the Rae Province, to the east. A scenario based on this crustal density structure is suggested for the evolution of the orogen. It calls for (1) the formation of a small ocean separating the Superiorand Rae provinces; (2) subduction of this ocean beneath the Rae Province; and (3) complete closure of the basin with over-thrusting of the Superior margin and, possibly, obduction of the Rae Province onto the Superior Province craton.